PENGARUH LATIHAN MULTIPLE BOX TO BOX JUMP TERHADAP KEKUATAN OTOT TUNGKAI DAN KEMAMPUAN SHOOTING PERMAINAN SEPAK BOLA - Mujriah, Mujriah (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
Limb muscle strength and shooting ability is a factor supporting the skills of playing an athlete's football. Problems in this research is the lack of muscle strength and shooting ability to play soccer at the club Lombok Smile selagalas FC in 2107. The formulation of the problem in this research is whether there is a Multiple Box Exercise To Box Jump Effect on leg muscle strength and shooting ability In football game On Lombok Smile selagalas FC year 2107. This research aims to know the effect of exercises Influence Exercise Multiple Box To Box Jump against leg muscle strength and shooting ability In the game of football on Lombok Smile selagalas FC in 2107. The research design used in this study using one group pre test post test design. The type of research used is experimental research. The population in this study is the player Lombok Smile Selagalas FC 2017 which amounted to 20 people.Teknik data collection using the test deeds and documentation. From the analysis results it can be concluded that there is Influence Exercise Multiple Box To Box Jump against leg muscle strength and shooting ability In the game of football on Lombok Smile selagalas FC year 2107. The results of data analysis using t test statistic showed on test leg muscle strength obtained value t count of 5.227> t table at a significant level of 5% DF (N-1) of 1.729 and the shooting ability test obtained t value value of 3.352> t table at a significant level of 5% DF (N-1) of 1.729. From result of analysis of data can be concluded that 1) there is influence of multiple box to box jump exercise to muscle strength of limb of year 2017. 2) there is influence of multiple box to box jump exercise to shooting ability year 2017